Рід Rosa L. у дослідженнях І.Ф. Шмальгаузена - Rubtsova, O.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The "Autographed herbarium of I.F. Schmalhausen" and other works of Schmalhausen were studied for detail examination of Rosa L. The results of the research are presented in the paper.